Optical Characterization Of GaN Thin Film Grown On Si(111) By Radio-Frequency Plasma-Assisted Molecular Beam Epitaxy. - L, S Chuah; Hassan, Z.; Abu Hassan, H (2007)

(untitled)
The wide band gap gallium nitride (GaN) based semiconductor system has great potential for applications in high-power, high-frequency, and hightemperature optoelectronic devices due to its superior properties, such as large breakdown field, high electron mobility, and thermal stability at elevated temperature.